Attenuation Value in Adrenal Incidentalomas: A Longitudinal Study - Ceccato, Filippo; Tizianel, Irene; Voltan, Giacomo; Maggetto, Gianmarco; Merante Boschin, Isabella; Quaia, Emilio; Crimì, Filippo; Scaroni, Carla (Frontiers in Endocrinology, 2021)
Context: A tendency to grow has been reported in adrenal incidentalomas. However, long-term data regarding attenuation value, a measure of lipid content, are not available. Aim: To collect radiological data (diameter in mm and attenuation value in Hounsfield units, HU) with computed tomography (CT) in adrenal incidentalomas, in order to compare baseline characteristics with the last follow-up imaging. Design: Longitudinal from 2002 to 2020. Setting: Referral University-Hospital center. Patients: 277 patients with 355 different cortical adenomas (baseline group) were evaluated at the first outpatient visit, the follow-up cohort consists in 181 patients with 234 adenomas (12-175 months after baseline). Inclusion criteria were conservative management and radiological features able to minimize malignancy or risk of progression. Main Outcome Measure: CT modification according to endocrine function: autonomous cortisol secretion (ACS) if cortisol >50 nmol/L after 1-mg dexamethasone test (DST). Results: At baseline CT mean diameter was 18.7 mm and attenuation value 0.8 HU (higher in ACS, 66 cases >10 HU), without modification in early imaging (12-36 months). The size increased over time (r=0.289), achieving the largest differences after at least 60-months of follow-up (mean diameter +2 mm and attenuation value -4 HU), combined with a reduction in the attenuation value (r=-0.195, especially in patients with ACS). Lipid-poor adenomas (>10 HU) presented a reduced cortisol suppression after 1-mg DST, an increase in size and the largest decrease in attenuation value during follow-up. Univariate analysis confirmed that larger adenomas presented reduced suppression after DST and increase in size during follow-up. Conclusions: Growth is clinically modest in adrenal incidentaloma: the first follow-up CT 5-year after baseline is a reasonable choice, especially in ACS. Mean density is increased in patients with ACS and overt hypercortisolism. Mean density reduces during follow-up in all adrenal adenomas, suggesting an increase in lipid content, especially in those with ACS.